Etika Profesi Akuntan dalam Menjaga Kredibilitas Informasi Keuangan di Era Globalisasi - Titi Lestari Lestari; Muchammad Najiich (INDO PUBLISHING, 2026)
Business globalization, the harmonization of international accounting standards, and the rapid development of information technology have increased the complexity of accounting practices and intensified ethical challenges that may threaten the credibility of financial information. This study aims to analyze the role of accountants’ professional ethics in maintaining transparency, integrity, and public trust in financial reporting in the era of globalization. The research employs a literature review method by examining relevant national and international journal articles, textbooks, professional codes of ethics, and accounting standards. The findings indicate that the consistent application of professional ethics serves as a fundamental foundation for professional judgment, ethical decision-making, and the enhancement of the credibility and public trust in financial information.